Dental Anatomy 2018
DOI: 10.5772/intechopen.71337
|View full text |Cite
|
Sign up to set email alerts
|

Dental Anatomical Features and Caries: A Relationship to be Investigated

Abstract: Dental caries is a multifactor disease affecting a significant number of people throughout the world. However, in recent decades the widespread availability of fluoride and other preventive measures have resulted in a decline in the prevalence of caries among children and young adults. Currently, it is accepted that most carious dental lesions are restricted to specific anatomical sites. The aim of this chapter is to review the influence of dental anatomy on dental caries development while taking into account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…The type of material used for restorations of molar teeth in this study have also been reported as intracoronal restorations in permanent molar teeth in previous studies [3,24,25]. The most prevalent type of material used for restoration was amalgam, a finding similar to that of previous reports [21].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The type of material used for restorations of molar teeth in this study have also been reported as intracoronal restorations in permanent molar teeth in previous studies [3,24,25]. The most prevalent type of material used for restoration was amalgam, a finding similar to that of previous reports [21].…”
Section: Discussionsupporting
confidence: 88%
“…Molars may be more prone to the demineralization of hard tissues occasioned by dental caries because of their peculiar anatomical features that enable them to perform the function of chewing and grinding. The dimension of these anatomical pits and features determine the extent of the demineralization process [3]. Deep pits and fissures give room for more food particles to be retained and for more production of acid by bacteria action.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by [ 31 , 36 , 38 ][ 39 ] found that posterior teeth had a higher plaque index and showed greater inflammation when compared to anterior teeth, hence they were at a greater risk of dental caries or periodontal disease. Several other researchers also concluded that posterior teeth were more prone to caries due to their anatomical form containing multiple fissures and grooves [ 40 ] or occasionally due to the presence of impacted third molars [ 41 ] causing increased incidence of decay at their proximal surface. The traditional need and mind set of restoring the complete dentition also played a role in the fact that most patients received 2nd molar-2nd molar restorations.…”
Section: Resultsmentioning
confidence: 99%
“…The mesiobuccal groove is a unique feature of mandibular first molars. It's a kind of sulcus that runs from the occlusal to buccal surfaces and is often unnoticed during dental examinations [24]. This narrow groove, though often shallow, can host a small but active bacterial population that can easily cause cavitation [25].…”
Section: Discussionmentioning
confidence: 99%